Between Western hegemony and local appropriateness of CSR practices in developing countries – The process of contextualization in the agricultural industry of Uganda. - Feldkamp, Niko; Wickert, Christopher; Katamba, David; Tindiwensi, Catherine; Seruma, Andrew (AGRI-QUEST, 2017)
In the past years, Corporate Social Responsibility (CSR) has been developed to be considered as a crucial tool that can significantly enhance development in southern countries. However, CSR has shortcomings, that were recently intensively discussed in research. In this regard, CSR was often associated with western hegemony. However, not only the CSR research is strongly characterized through a western perspective. Also, developed CSR practices in emerging countries are driven by western-hosted multinational enterprises (MNE) or standards as for example ISO 26000, that were developed in a western context. Previous studies have shown, that such understanding did not always lead to indented benefits in emerging countries. Even though previous research emphasized the existing tension between international standards and local appropriateness, an examination of the process of contextualization has not been established yet. Therefore, this work aims on developing a concept, that leads to positive impacts by implementing CSR practices in the developing country context. For that purpose, an explanatory study with a trip of in total three weeks to Uganda has been conducted. Thus, local voices and perspectives could be incorporated that can provide a valuable supplement to the current literature. Finally, the results show a concept of contextualization of western based CSR practices in a developing country context.
Keywords: Corporate social responsibility (CSR); Western hegemony; Developing countries; Explanatory study